Impact of risk factors, early rehabilitation and management of lymphedema associated with breast cancer: a retrospective study of breast Cancer survivors over 5 years - Slobodan Tomić; Goran Malenković; Ermina Mujičić; Armin Šljivo; Sanja D. Tomić (BMC Women's Health, 2024)
Abstract Background Breast cancer-related lymphedema (BCRL) is a potentially disabling and often irreversible consequence of breast cancer treatment, caused by the mechanical incompetence of the lymphatic system, resulting in reduced drainage capacity and functional overload due to an excessive volume of interstitial fluid surpassing the system’s transport capacity in the arm. We wanted to determine the impact and explore the differences in independent risk factors for the occurrence of BCRL; incidence of BCRL over a five-year period at the Institute of Oncology Vojvodina in Sremska Kamenica and to answer the research question regarding the influence of the prehabilitation program on the overall incidence of BCRL during the observed five-year period. Methods From 2014 to 2018, a retrospective study was conducted at the Institute of Oncology of Vojvodina in Sremska Kamenica, analyzing female patients who had undergone breast cancer surgery. Results The study included 150 breast cancer patients who developed secondary lymphedema following surgery with the mean age of 59.2 ± 11.3 years. Fluctuations in hospitalization rates were observed over the five-year period, with the highest number of admissions in 2014 (24.0%) and a decline in 2018 (14.0%). The most common surgical procedure performed was left quadrantectomy (24.0%), followed by right quadrantectomy (20.0%) and left amputation (15.3%). The mean number of removed lymph nodes was 15.2 ± 6.1, with no statistically significant association between the number of removed lymph nodes and the manifestation of secondary lymphedema. The severity of secondary lymphedema varied based on patient age, with a higher incidence of moderate and severe lymphedema observed in patients aged 61 years and older. Patients who underwent radical surgery were more likely to experience severe lymphedema compared to those who had conservative surgery, although this difference was not statistically significant. Conclusion In our study, the type of surgery, elapsed time since surgery, and the number of removed lymph nodes were not influencing factors for the occurrence of BCRL. However, concerning its severity, a greater number of systemic therapy modalities combined with radiotherapy were associated with a more frequent occurrence of mild and moderate BCRL. Also, the severity of BCRL varied among different age groups, with a higher incidence of moderate and severe lymphedema observed in patients aged 61 years and older. Ultimately, improving the quality of life for individuals affected by secondary lymphedema remains a crucial goal in the field of oncology.